Analisis Efektivitas Manajemen Pengelolaan Sampah Perkotaan Melalui Pendekatan Sistem Input Proses Output Outcome (IPOO) Pada Dinas Lingkungan Hidup Dan Kebersihan Kota Pekanbaru - Muhammad Adrian Perdana; Ariandi A Zulkarnain (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2026)
Urban waste management is one of the primary challenges faced by major cities in Indonesia, including Pekanbaru. The population growth in Pekanbaru, which reached 1,064,566 people in 2016, is directly proportional to the increasing volume of waste generation that requires management. This study aims to analyze the effectiveness of waste management at the Pekanbaru City Environmental and Sanitation Department (DLHK) using the Input–Process–Output–Outcome (IPOO) system approach. The research method employed is descriptive qualitative, with data collection techniques including documentation studies, interviews, and observations. The results indicate that the waste fleet's transport capacity only reaches 48.2% of the ideal requirement, leaving the volume of handled waste far below the actual generation. There is a gap between available inputs, ongoing processes, resulting outputs, and expected outcomes in Pekanbaru's waste management. It is necessary to at least double the fleet capacity, strengthen regulations, and increase community participation.